Proposing a trend-based time-varying approach to assess climate- and human-induced impacts on streamflow. Issue 12 (9th September 2020) - Li, Jianfeng; Shi, Xiaogang; Chen, Yongqin David; Zhang, Lu
ABSTRACT: The conventional abrupt change-based assessments of climate- and human-induced impacts on streamflow require the existence of change point(s) and stationarity assumption. However, hydrological conditions may not change abruptly at a certain time, but rather evolve gradually over a period. We propose a trend-based time-varying approach that does not require these prerequisites to assess the climate- and human-induced impacts on hydrological conditions in the Pearl River Basin (PRB), China, which can be applied in other basins. The trend-based time-varying approach detects human activities exert a significant seasonal regulation on streamflow (i.e. 113% of the decreases in the wet season and 93% of the increases in the dry season) and 101% of the reductions in flood peaks in the East River Basin, the sub-basin with the highest ratio of total reservoir storage capacity to river discharge in the PRB. Climate change contributes to 77% of the increases in flood peaks in the West River Basin, a large sub-basin with lower flood control levels.